Metode Pengajaran pada Critical Paedagogis - Budi Harjo (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2022)
Based on the problem of the article, the formative assessment model improves critical thinking skills in learning. The formative assessment model has several weaknesses in the assessment that has not been integrated into the learning process. students' learning difficulties have not been observed properly. Assessment tools are designed by teachers to develop critical thinking skills in learning. Students' assignments are rarely given corrective feedback to find out the strengths and weaknesses of student learning outcomes. There is no formative assessment model for critical thinking skills in learning. There is no guide to the formative assessment model for critical thinking skills in learning that can be used by teachers to develop critical thinking skills in learning. The shortcomings in the Formative assessment model need to be addressed at the reference level. This is what started this paper as the main material for discussing critical skills affecting the pedagogical learning.